4: Prolonged Tourniquet Use Following Blast Related Lower Extremity Injuries Increase Heterotopic Ossification in a Pre-clinical Model. (July 2021) - Strong, Amy L.; Levi, Benjamin; Mares, John; Davis, Thomas A.; Spreadborough, Philip J.
Abstract : Purpose: Traumatic heterotopic ossification (tHO) has become a signature pathology affecting wounded military personnel who have sustained blast-associated traumatic amputations during the recent conflicts in Iraq and Afghanistan. Heterotopic ossification is characterized by the abnormal development of mature bone depositions in extra-skeletal sites such muscle, tendon, and soft tissues, leading to impaired wound healing, pain, reduced range of motion, and limited use of prostheses. While many factors influence the formation of tHO, the extended use of tourniquets to limit catastrophic hemorrhage during prolonged field care (PFC) has not been explored. Herein, we investigate the impact of tourniquet use following blast-related injury on ectopic bone formation. Methods : Utilizing an established pre-clinical model of blast-associated complex lower limb injury and traumatic amputation, we evaluated the effects of extended tourniquet use on tHO formation. Male rats (11-12-week-old) were subjected to blast overpressure exposure, femur fracture, and soft tissue crush injury. A pneumatic tourniquet (250-300mmHg) was applied to the injured limbs for either 90- and 150-minutes followed by trans-femoral amputation. Limbs were assessed for HO formation using microCT. Analysis of muscle/soft-tissue osteogenesis-related gene transcripts and multiple serum inflammatory mediators were measured by using qRT-PCR and Luminex multiplex assays, respectively. Results : At 12 weeks, volumetric analysis with microCT imaging revealed an 70% increase in total bone formation (P=0.007, n=11) near the site of injury in rats subjected to 150-minutes of tourniquet time compared to rats with no tourniquet time in the setting of blast-injuries. Rats subjected to 150-minute tourniquet usage and blast injury had increased expression of osteochondrogenic genes including Bmp2 (5.4-fold increase, P=0.01) as early as 6 hours post-injury while Hif1α (4.2-fold increase, P<0.01), Sox9 (2.8-fold increase, P<0.01), Runx2 (8.2-fold increase), and Bmp2 (7.7-fold increase, P<0.02) remained elevated for 7 days. Analysis of cytokines and chemokines in the serum demonstrated increased expression of key analytes in the tourniquet group above that induced by traumatic amputation alone in the control group in factors including IL-1 (22-44%, P<0.005) and IL-6 (13-69% p<0.03) between 6 hrs and POD7. Conclusions : These findings suggest that extended tourniquet time leads to both significant increases in key transcription factors associated with early endochondral bone formation, as well as increased systemic inflammatory mediators. Increased expression of Hif1α with prolonged tourniquet use also demonstrates the importance of tissue hypoxia and Hif1α signaling in combat applicable tHO and the potential development of targets for therapeutic inhibition. This data supports mechanisms by which extended tourniquet times under PFC conditions could result in increased local neuromuscular dysfunction and systemic inflammation, resulting in increased local tissue injury and potential further functional loss secondary to tHO in wounded military personnel.